A case report of Talaromyces marneffei Oro-pharyngo-laryngitis: A rare manifestation of Talaromycosis - Thanyarak Wongkamhla (2020)
© 2019 The Author(s). Background: The incidence of Taralomyces marneffei infection in HIV-infected individuals has been decreasing, whereas its rate is rising among non-HIV immunodeficient persons, particularly patients with anti-interferon-gamma autoantibodies. T. marneffei usually causes invasive and disseminated infections, including fungemia. T. marneffei oro-pharyngo-laryngitis is an unusual manifestation of talaromycosis. Case presentation: A 52-year-old Thai woman had been diagnosed anti-IFNɣ autoantibodies for 4 years. She had a sore throat, odynophagia, and hoarseness for 3 weeks. She also had febrile symptoms and lost 5 kg in weight. Physical examination revealed marked swelling and hyperemia of both sides of the tonsils, the uvula and palatal arches including a swelling of the epiglottis, and arytenoid. The right tonsillar biopsy exhibited a few intracellular oval and elongated yeast-like organisms with some central transverse septum seen, which subsequently grew a few colonies of T. marneffei on fungal cultures. The patient received amphotericin B deoxycholate 45 mg/dayfor 1 weeks, followed by oral itraconazole 400 mg/day for several months. Her symptoms completely resolved without complication. Conclusion: In patients with anti-IFN-ɣ autoantibodies, T. marneffei can rarely cause a local infection involving oropharynx and larynx. Fungal culture and pathological examination are warranted for diagnosis T. marneffei oro-pharyngo-laryngitis. This condition requires a long term antifungal therapy.